Assessment of toxicity profile of Mollusca hemolymph: Insight into its potential biocompatibility and anti-biofilm efficacy - Minati Soren; Sambit Kumar Mishra; Awdhesh Kumar Mishra; Pradipta Ranjan Rauta; Jibanjyoti Panda; Sarvesh Rustagi; Seydur Rahman; Yugal Kishore Mohanta; Debasis Nayak (Kuwait Journal of Science)
Traditional food habits followed by indigenous populations have a huge potential in providing nutrition to the world community aided with nutritional supplements. The phylum mollusca can provide alternative supplements for food and biochemical potentials. In the current investigation, the hemolymph of Pomacea canaliculata, Achatina fulica, and Lamellidense marginalis was collected through the heart puncture method and they were characterized through fourier transformation infrared spectroscopy (FTIR), gas chromatography-mass spectroscopy (GC-MS), Inductively coupled plasma atomic emission spectroscopy (ICP-OES), antioxidant activity, hemolysis, antimicrobial and antibiofilm activity. The collected hemolymph demonstrated a prominent 65 kDa protein band in Sodium Dodecyl Sulfate- Poly Acrylamide Gel Electrophoresis (SDS-PAGE). The hemolymph samples exhibited strong antioxidant activity against standard free radicals. They were found to be highly haemocompatible through hemolysis and hemagglutination assay. The hemolymph exhibited antimicrobial activity against the pathogenic Escherichia coli, Pseudomonas aeruginosa and Vibrio cholerae. All the test samples demonstrated high biofilm inhibiting activity through tube assay and Congo red assay. The hemolymph extracts confirmed dose dependent cell toxicity against the A431 skin carcinoma cells. Hence, this study provides an insight into the potential application of the hemolymph in various biomedical applications, which can be validated through future in vitro experimentations.